Neurological improvement is associated with neck pain attenuation after surgery for cervical ossification of the posterior longitudinal ligament - Masao Koda (Nature Portfolio, 2021)
Abstract Although favourable surgical outcomes for myelopathy caused by cervical ossification of the posterior longitudinal ligament (OPLL) have been reported, factors significantly associated with post-operative neck pain attenuation still remain unclear. The primary aim of the present study was to determine factors significantly associated with post-operative neck pain attenuation in patients with cervical OPLL using a prospective multi-centre registry of surgically treated cervical OPLL. Significant postoperative neck pain reduction (50% reduction of neck pain) was achieved in 31.3% of patients. There was no significant difference in neck pain attenuation between surgical procedures. Statistical analyses with univariate analyses followed by stepwise logistic regression revealed neurological recovery as a factor having a significant positive association with post-operative neck pain attenuation (p = 0.04, odds ratio 5.68 (95% confidence interval: 1.27–22.2)). In conclusion, neurological recovery was an independent factor having a significant positive association with post-operative neck pain attenuation in patients with cervical myelopathy caused by OPLL who underwent cervical spine surgery.